(untitled) - Miller, Roy Andrew (Tokyo, 1967)
The book presupposes no previuos knowledge of Japanese language or script, and will be especially useful as a reference cource or as supplementary reading for students of Japanese or Chinese language and culture, Far Eastern history, and general linguistics.
Keywords: Japanese language